Assessment of Student Attitudes in German Writing Learning Based on 21st Century Skills - Purwanto, Anim; Lustyantie, Ninuk; Murtadho, Fathiaty (Journal of Education Method and Learning Strategy, 2024)
Students' attitudes towards language learning have two sides, either motivating or even diminishing their learning enthusiasm. The main objectives of this research are first, to assess students' attitudes in learning descriptive writing in German language; second, to develop an attitude assessment model in writing based on 21st-century competencies. This research adopts an exploratory descriptive approach with a sample of 35 high school students. Data were collected through attitude assessment sheets referring to 21st-century educational competencies, namely critical thinking skills, creativity, communication, and collaboration. Data analysis involved categorizing assessment results using average scores from all respondents. The findings indicate a tendency that most students achieve a good level in critical thinking, creativity, communication, and collaboration aspects in learning to write in German. However, there is still a small portion of students who reach a very good level, indicating a gap in students' abilities. The attitude assessment model developed in this research significantly contributes to teachers in measuring students' progress and helps prepare students to become critical, creative, and inspirational decision-makers in various learning situations and daily life. The use of this attitude assessment model shifts the learning paradigm from emphasizing outcomes to developing students' relevant skills for future demands.